ACCOUNTING INFORMATION SYSTEM USING THE ASSETS DEPRECIATION IN GENERAL BULOG CENTRAL KALIMANTAN REGIONAL DIVISION - Licantik Licantik (Universitas Palangka Raya, 2014)
Accounting information system (AIS) is an information system that change the data ofbusinnes transaction become data and financial information that is used for the user. To make thefixed assest datas, it needs a syste where the system is accounting information system (AIS)General Company of Bulog Devision in Central Kalimantan in the process for the greater part stillmanually, which used Microsoft Excel as a counting tool and there is no intergration from journal,ledger, balance report, profit and lose report, equity report/ the change of capital report in theassest reduction counting. So that, it pursues the presentation of financial report because there is apossibility of mistake that happened in the process of writing so that the data of fixed assest notharmony and need a long time and fixed assets to do reduction counting with that condition, itneeds a system that able to solve the problems though the accountant information system (SIA) withassets reduction methode.Accounting information system (AIS) with assets reduction methode is built with waterfallsoftware development lifecycle by data flow diagram (DFD) and entity relationship diagram (ERD)structured desighn, which is implemented using databasee tool Microsoft SQL server 2000 andsoftware tool visual basic 6.0.Accounting information system (AIS) with assets reduction methode has recording facilitiesaccount code, to see the result of amount of current year capital, fixed assets recording, thecounting of fixed assets with straight line methode with estimate the residue score, journal andledger recording, the output counting result and to prepare and print the recording of jour halevery month and year, reduction recording list, ledger recording, profit and loss recording,balance and equity recording.